Image‐Guided Magnetic Thermoseed Navigation and Tumor Ablation Using a Magnetic Resonance Imaging System (Adv. Sci. 12/2022). Issue 12 (25th April 2022) - Baker, Rebecca R.; Payne, Christopher; Yu, Yichao; Mohseni, Matin; Connell, John J.; Lin, Fangyu; Harrison, Ian F.; Southern, Paul; Rudrapatna, Umesh S.; Stuckey, Daniel J.; Kalber, Tammy L.; Siow, Bernard; et al.
Abstract : Minimally Invasive Image‐Guided Ablation Concept An artist's impression of the minimally invasive image‐guided ablation (MINIMA) concept, whereby the magnetic field gradients generated by an MRI scanner are used to navigate a ferromagnetic thermoseed through tissue to a target, where it is remotely heated to deliver thermal ablation. More details can be found in article number 2105333 by Rebecca R. Baker, Mark F. Lythgoe, and co‐workers.